Epidemiology of Gram-negative bacteria during coronavirus disease 2019. What is the real pandemic?. Issue 6 (3rd December 2022) - Brink, Adrian J.; Richards, Guy; Tootla, Hafsah; Prentice, Elizabeth
Abstract : Purpose of review: Bacterial infections play a key role in hospital outcomes during the coronavirus disease 2019 (COVID-19) pandemic. Nonetheless, the global impact on the epidemiology of Gram-negative bacteria (GNB) and antibiotic resistance has not been clearly established. Recent findings: Multiple limitations exist in the current literature, in that substantial variability was observed with regard to methodology. Notwithstanding the heterogeneity, the evidence suggests that the COVID-19 pandemic had a substantial negative impact on global epidemiology with an increase in hospital-onset infections, associated with GNB. Similarly, an alarming increase in resistant GNB compared to prepandemic rates, was apparent. This was most evident for carbapenemase-producing Klebsiella pneumoniae (bloodstream infections), carbapenem-resistant Pseudomonas aeruginosa (ventilator-associated pneumonia), and carbapenem-resistant Acinetobacter baumannii (all infections). Significant variations were most apparent in the large, system-wide regional or national comparative assessments, vs. single-centre studies. Categorizing concurrent bacteria as co- or secondary-infections may be paramount to optimize standard of care. Summary: The data from most studies signal the probability that COVID-19 accelerated resistance. However, multiple limitations intrinsic to interpretation of current COVID-19 data, prevents accurately quantifying collateral damage on the global epidemiology and antibiotic resistance amongst GNB. It is likely to be substantial and renewed efforts to limit further increases is warranted.